Preventable maternal mortality: Geographic/rural-urban differences and associated factors from the population-based maternal mortality surveillance system in China - Zhou Rong; Li Mingrong; Li Qi; Wang He; Zeng Weiyue; Li Xiaohong; Zhu Jun; Dai Li; Liang Juan; Wang Yanping (BMC, 2011)
Abstract Background Most maternal deaths in developing countries can be prevented. China is among the 13 countries with the most maternal deaths; however, there has been a marked decrease in the maternal mortality ratio (MMR) over the last 3 decades. China's reduction in the MMR has contributed significantly to the global decline of the MMR. This study examined the geographic and rural-urban differences, time trends and related factors in preventable maternal deaths in China during 1996-2005, with the aim of providing reliable evidence for effective interventions. Methods Data were retrieved from the population-based maternal mortality surveillance system in China. Each death was reviewed by three committees to determine whether it was avoidable. The preventable maternal mortality ratio (PMMR), the ratios of PMMR (risk ratio, RR) and 95% confidence intervals (CI) were used to analyze regional disparities (coastal, inland and remote regions) and rural-urban variations. Time trends in the MMR, along with underlying causes and associated factors of death, were also analysed. Results Overall, 86.1% of maternal mortality was preventable. The RR of preventable maternal mortality adjusted by region was 2.79 (95% CI 2.42-3.21) and 2.38 (95% CI: 2.01-2.81) in rural areas compared to urban areas during the 1996-2000 and 2001-2005 periods, respectively. Meanwhile, the RR was the highest in remote areas, which was 4.80(95%CI: 4.10-5.61) and 4.74(95%CI: 3.86-5.83) times as much as that of coastal areas. Obstetric haemorrhage accounted for over 50% of preventable deaths during the 2001-2005 period. Insufficient information about pregnancy among women in remote areas and out-of-date knowledge and skills of health professionals and substandard obstetric services in coastal regions were the factors frequently associated with MMR. Conclusions Preventable maternal mortality and the distribution of its associated factors in China revealed obvious regional differences. The PMMR was higher in underdeveloped regions. In future interventions in remote and inland areas, more emphasis should be placed on improving women's ability to utilize healthcare services, enhancing the service capability of health institutions, and increasing the accessibility of obstetric services. These approaches will effectively lower PMMR in those regions and narrow the gap among the different regions.